Pelatihan Penyusunan Laporan Keuangan Pada Pusat Koperasi Yasmin PW Fatayat Nahdlatul Ulama Provinsi Lampung - Masthuroh Masthuroh (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Community service activities to provide training on preparing financial reports at the Yasmin Fatayat Nahdlatul Ulama Cooperative Center, Lampung Province. Activity methods include material presentation, discussion, training and mentoring. series of activities: presenting material on preparing financial reports, the aim of this training socialization is that it is hoped that the central management of the Yasmin PW Fatayat NU cooperative, Lampung Province, can prepare financial reports every month.